(untitled) (Research, Society and Development, 2021)
The present work has as its theme congenital syphilis and nursing care, aiming to delimit an epidemiological profile of reported cases in the state of Paraná. Congenital syphilis is an STI that occurs through vertical transmission between mother and child during pregnancy, breastfeeding or childbirth, which can be avoided through proper treatment, efficiently guiding through nursing care. This research constitutes a quantitative, bibliographical and exploratory research, which brings the analysis of the data made available in SINAN of the notified cases of congenital syphilis from the years 2010 to 2020, bringing as a result the understanding of the problem of syphilis in the state of Paraná, which needs a careful look at the construction of campaigns and preventive interventions to change this scenario.